Rotavirus gastroenteritis hospitalization rates and correlation with rotavirus vaccination coverage in Sicily: Universal rotavirus vaccination in Sicily - Restivo, Vincenzo; Caracci, Francesca; Sannasardo, Claudia Emilia; Scarpitta, Francesco; Vella, Carlotta; Ventura, Gianmarco; Tramuto, Fabio; Costantino, Claudio (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the works: Rotavirus (RV) is considered the main cause of gastroenteritis in children from 0 to 59 months and vaccination represents the only strategy to prevent hospitalizations due to RV. In 2013 Sicilian Region introduced universal RV vaccination for all newborns. The present study aims to estimate the reduction rotavirus gastroenteritis (RVGE) hospitalization rates among Sicilian children and their relations with vaccination coverages of the nine Sicilian Local Health Units (LHUs). Methods: Were analyzed hospital discharge records including a diagnosis of RVGE occurred from January 2009 to December 2017 in hospitalized children aged 0 to 59 months, residents in Sicily. Were reported data on complete RV vaccination cycles among Sicilian children under 12 months of age (vaccination coverage). Results: A 49.2% overall reduction of RVGE hospitalization rates was reported after RV vaccination introduction. A more considerable reduction of hospitalization rates was observed among children aged 0 to 11 months (-61.4%), followed by children aged 12-23 months (-51.2%) and 24-35 months (-48.8%). In all the nine Sicilian Local Health Units (LHUs), a reduction of RVGE hospitalization rates was observed after RV vaccine implementation. Conclusions: This study demonstrated the significant impact of RV vaccination on RVGE hospitalization rates in Sicily, especially among children aged 0 to 23 months. The reduction in RVGE hospitalization rates observed in the Sicilian LHUs after universal vaccination program implementation, were generally higher or consistent with average vaccination coverage reported from 2013 to 2017.